THE EFFECT OF ADOLESCENT ATTITUDES ON KARANG TARUNA IN HANDLING PROBLEMS TOWARD ADOLESCENTS IN THE DEVELOPMENT PERIOD - Suharma Suharma; Ramli A Rahman; Ernalia Lia Syaodih; Yana Sundayani; Popon Sutarsih; Yeane EM Tungga (Politeknik Kesejahteraan Sosial Bandung, 2020)
Adolescence is the most important development period for an individual, in fact, it is a period filled by changes and vulnerable to the emergence of the problems. Forum of Karang Taruna has a strategic role as a means of youth participation in an effort to make social adjustments so that they can deal with the problems encountered during life development. This research was conducted to gain a deep understanding and thorough about the influence of adolescent attitudes about the Karang Taruna on handling problems faced by youth in the development phase of their life. This research used a quantitative approach with a survey explanatory research population were teenagers aged 12 to 21 years. Measuring instrument research used a Likert scale. The technique of collecting data used questionnaires and documentation study. Data were analyzed using path analysis. Adolescent attitudes toward Karang Taruna have a significant effect on the involvement of adolescents in Karang Taruna activities. The amount of influence adolescent attitudes about the Karang Taruna on the involvement of adolescents in Karang Taruna amounted to 61.40%. The results also showed that the attitude of teenagers towards Karang Taruna has a significant influence on the Settlement of the problems faced by an adolescent in their life development through variable among adolescent involvement in Karang Taruna. The number of adolescent attitudes influences Karang Taruna through the involvement of adolescents in Karang Taruna on the handling of problems faced by an adolescent in the developmental period of their life amounted to 85.80%. Karang Taruna can be used as a means to develop the activity and creativity of adolescents in handling the problems encountered in the development phase of their life. However, there are six main problems faced by Karang Taruna including; (1) an inactive member; (2); a caretaker capacity in managing Karang Taruna; (3) there is no clear work programme; (4) The board of Karang Taruna inactivity; (5) the absence of funding sources; and (6) less variation in the activities of Karang Taruna that does not appeal to its members, especially for passive members.